THE DUAL SUPERVISION MODEL AS A GOVERNANCE FRAMEWORK FOR ISLAMIC FINANCIAL INSTITUTIONS - Khairunnisa, Ashma; Arifin, Zainal; Saleh, Imran; Hermawan, Riko (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2026)
The rapid growth of the Islamic financial industry has not been fully accompanied by the strengthening of ethical integrity and Sharia governance quality. This study examines the concept of dual supervision as an integrative model that combines regulatory oversight and taqwa-based internal control within Islamic economic systems. Using a qualitative library research approach, this study analyzes classical and contemporary Islamic legal thought, particularly drawing on Mausu’ah Qadhaya Fiqhiyyah Mu’ashirah by Dr. Ali al-Salus, along with relevant literature on Islamic governance and financial analysis. The findings indicate that regulatory supervision ensures formal compliance with Sharia standards and institutional procedures, while it remains insufficient in preventing moral hazards and ethical violations. Conversely, taqwa functions as an internal spiritual mechanism that fosters accountability, integrity, and ethical responsibility among economic actors. The integration of both dimensions produces a dual supervision framework that strengthens Sharia compliance, enhances governance effectiveness, and supports sustainable Islamic financial development. Furthermore, the model is relevant to contemporary challenges such as financial technology innovation, regulatory fragmentation, and increasing complexity in Islamic financial transactions. This study contributes to the development of Islamic governance theory and offers a conceptual framework for improving both Sharia compliance and ethical performance in Islamic financial institutions.